High Resolution Underway Nitrous Oxide Measurements (atmosphere) during METEOR cruise M98 - Damian L Arévalo-Martínez; Hermann W Bange (PANGAEA, 2019)
The Benguela Upwelling System (BUS) is the most productive of all eastern boundary upwelling ecosystems and it hosts a well-developed oxygen minimum zone. As such, the BUS is a potential hotspot for production of N2O, a potent greenhouse gas derived from microbially driven decay of sinking organic matter. Yet, the extent at which near-surface waters emit N2O to the atmosphere in the BUS is highly uncertain. Here we present the first high-resolution surface measurements of N2O across the northern part of the BUS (nBUS).We found strong gradients with a threefold increase in N2O concentrations near the coast as compared with open ocean waters. Our observations show enhanced sea-to-air fluxes of N2O (up to 1.67 nmol m-2 s-1) in association with local upwelling cells. Based on our data we suggest that the nBUS can account for 13% of the total coastal upwelling source of N2O to the atmosphere
In supplement to: Arévalo-Martínez, Damian L; Steinhoff, T; Brandt, Peter; Körtzinger, Arne; Lamont, Tarron; Rehder, Gregor; Bange, Hermann W (2019): N2O Emissions From the Northern Benguela Upwelling System. Geophysical Research Letters, 46(6), 3317-3326, https://doi.org/10.1029/2018GL081648